PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN TEMATIK MENGGUNAKAN MODEL DISCOVERY LEARNING DI SEKOLAH DASAR - Rosada Rosada; Syambasril Syambasril; Siti Halidjah (Universitas Tanjungpura, 2020)
AbstractThis reseach aims to describe the increase in student learning outcomes using the discovery learning model in class V public Elementary School 14 South Pontianak. This research used a descriptive method. Subject in this research were teacher and all student of class V Elementary School of State 14 South Pontianak of amounted to 24 students. Data collection instruments that is observasing sheets and document observation sheets. The implementation of teacher learning by applying the discovery learning model in thematic learning was good because the teacher carried out learning in accordance with the indicators of implementing thematic learning and the RPP made. The average value of pre cycle students cognitive learning outcomes was 54,58 with the category of less, in the first cycle of 61,90 with a sufficient category, and in the second cycle the average value was 83,81 in good category. The average value of pre cycle psychomotor learning outcomes was 57,14 with the category of less, in the first cycle 72,40 with sufficient category, and the second cycle with an average value of 85,95 with good category. Thus, the use of discovery learning models can improve the thematic learning outcomes of class V Elementary School 14 South Pontianak. Keywords: Discovery Learning, Improvement, Learning Outcomes